Insertion State of Modular Protein Nanopores Into a Membrane - Larimi, Motahareh Ghahari (Biochim Biophys Acta Biomembr, 2021)
In the past decade, significant progress has been made in the development of new protein nanopores. Despite these advancements, there is a pressing need for the creation of nanopores equipped with relatively large functional groups for the sampling of biomolecular events on their extramembranous side. Here, we designed, produced, and analyzed protein nanopores encompassing a robust truncation of a monomeric β-barrel membrane protein. An exogenous stably folded protein was anchored within the aqueous phase via a flexible peptide tether of varying length. We have extensively examined the pore-forming properties of these modular protein nanopores using protein engineering and single-molecule electrophysiology. This study revealed distinctions in the nanopore conductance and current fluctuations that arose from tethering the exogenous protein to either the N terminus or the C terminus. Remarkably, these nanopores insert into a planar lipid membrane with one specific conductance among a set of three substate conductance values. Moreover, we demonstrate that the occurrence probabilities of these insertion substates depend on the length of the peptide tether, the orientation of the exogenous protein with respect to the nanopore opening, and the molecular mass of tethered protein. In addition, the three conductance values remain unaltered by major changes in the composition of modular nanopores. The outcomes of this work serve as a platform for further developments in areas of protein engineering of transmembrane pores and biosensor technology.